Microbial Etiologies and Clinical Characteristics of Children Seeking Emergency Department Care Due to Vomiting in the Absence of Diarrhea. (16th May 2021) - Freedman, Stephen B; Xie, Jianling; Lee, Bonita E; Ali, Samina; Pang, Xiao-Li; Chui, Linda; Zhuo, Ran; Vanderkooi, Otto G; Tellier, Raymond; Funk, Anna L; Tarr, Phillip I
Abstract: Background: As children with isolated vomiting are rarely able to provide a specimen suitable for routine pathogen testing, we have limited knowledge about their infecting pathogens. Methods: Between December 2014 and August 2018, children <18 years old with presumed acute gastroenteritis who presented to 2 emergency departments (EDs) in Alberta, Canada, were recruited. Eligible participants had ≥3 episodes of vomiting and/or diarrhea in a 24-hour period, <7 days of symptoms, and provided a rectal swab or stool specimen. We quantified the proportion of children with isolated vomiting in whom an enteropathogen was identified, and analyzed clinical characteristics, types of enteropathogens, resources used, and alternative diagnoses. Results: Of the 2695 participants, at the ED visit, 295 (10.9%), 1321 (49.0%), and 1079 (40.0%) reported having isolated diarrhea, vomiting and diarrhea, or isolated vomiting, respectively. An enteropathogen was detected most commonly in those with vomiting and diarrhea (1067/1321; 80.8%); detection did not differ between those with isolated diarrhea (170/295; 57.6%) and isolated vomiting (589/1079; 54.6%) (95% confidence interval of the difference: −3.4%, 9.3%). Children with isolated vomiting most often had a virus (557/1077; 51.7%), most commonly norovirus (321/1077; 29.8%); 5.7% (62/1079) had a bacterial pathogen. X-rays, ultrasounds, and urine tests were most commonly performed in children with isolated vomiting. Alternate etiologies were most common in those with isolated vomiting (5.7%; 61/1079). Conclusions: The rate of enteropathogen identification in children with isolated vomiting using molecular diagnostic tests and rectal swabs is substantial. Molecular diagnostics offer an emerging diagnostic strategy in children with isolated vomiting. Abstract : Forty percent of children with presumed acute gastroenteritis present with isolated vomiting. An enteropathogen can be identified in 54.6% of such children brought for emergency department care. Microbial evaluations may reduce performance of other diagnostic tests while improving diagnostic accuracy.